Developing a tailored substance use intervention for youth exiting foster care. (March 2018) - Braciszewski, Jordan M.; Tzilos Wernette, Golfo K.; Moore, Roland S.; Tran, Tanya B.; Bock, Beth C.; Stout, Robert L.; Chamberlain, Patricia; Vose-O'Neal, Adam
Abstract: Youth who are aging out of the foster care system face significant barriers to accessing substance use treatment. Mobile interventions have shown efficacy for several mental and physical health issues and may be helpful in overcoming barriers facing foster youth with substance use problems. A program (iHeLP) for substance use reduction was developed that used a computerized screening and brief intervention (SBI) followed by six months of dynamically-tailored text messages. The program was shown to focus groups of youth (N = 24) ages 18–19 who recently left foster care and had moderate to severe substance use risk. Focus group feedback was used to modify iHeLP prior to delivery in an open trial (N = 16). Both study phases included assessments of feasibility and acceptability; the open trial also included assessments of substance use outcomes at 3 and 6 months. Focus groups indicated a high level of acceptability for the proposed intervention components. Of those screened for the open trial, 43% were eligible and 74% of those eligible enrolled, indicating good feasibility. Retention through the final follow-up was 59%, and drop out was associated with involvement in the criminal justice system. Participant ratings for liking, ease of working with, interest in and respectfulness of the SBI were high. Satisfaction ratings for the texting component were also high. A computerized brief screening intervention for substance use risk reduction together with tailored text messaging is both feasible and highly acceptable among youth who have recently aged-out of foster care.